2000
DOI: 10.1186/1297-9686-32-5-511
|View full text |Cite
|
Sign up to set email alerts
|

A first genotyping assay of French cattle breeds based on a new allele of the extension gene encoding the melanocortin-1 receptor (Mc1r)

Abstract: The seven transmembrane domain melanocortin-1 receptor (Mc1r) encoded by the coat color extension gene ( E ) plays a key role in the signaling pathway of melanin synthesis. Upon the binding of agonist (melanocortin hormone, α -MSH) or antagonist (Agouti protein) ligands, the melanosomal synthesis of eumelanin and/or phaeomelanin pigments is stimulated or inhibited, respectively. Different alleles of the extension gene w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
7

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 0 publications
3
47
0
7
Order By: Relevance
“…The 5 -untranslated region (5 -UTR) of the sheep MC1R gene (composed of only one exon as in all other mammals) was deduced aligning the obtained MC1R sequences with that of the cattle MC1R cDNA (GenBank accession number: AF445642; Rouzaud et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 5 -untranslated region (5 -UTR) of the sheep MC1R gene (composed of only one exon as in all other mammals) was deduced aligning the obtained MC1R sequences with that of the cattle MC1R cDNA (GenBank accession number: AF445642; Rouzaud et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…DNA was extracted using a standard phenol-chloroform protocol for blood, the Wizard ® Genomic DNA Purification kit for blood and milk (Promega Corporation, Madison, WI, USA) or rapid extraction methods for milk and hair roots (Russo et al, 2007). Primers for MC1R amplification and sequencing (Table 1) were designed with Primer 3 (Whitehead Institute for Biomedical Research, Cambridge, MA, USA) from the published bovine, sheep and goat MC1R gene sequences (GenBank accession numbers: AF445641, Y13965, and FM212940, respectively; Rouzaud et al, 2000;Våge et al, 1999;Fontanesi et al, 2009a). PCR was performed using a TGradient thermal cycler (Biometra, Göttingen, Germany) or a PT-100 thermal cycler (MJ Research, Watertown, MA, USA) in a volume of 20 L containing 10-100 ng DNA template, 1 U DNA EuroTaq DNA polymerase (EuroClone Ltd., Paington, Devon, UK), 1× PCR Buffer, 2.5 mM dNTPs, 10 pmol of each primer and optimised MgCl2 concentrations (from 1.0 to 2.0 mM).…”
Section: Dna Extraction and Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Gain-of-function and loss-of-function mutations of the MC1R gene determining dominant or partially dominant black/dark and recessive or partially recessive red/yellow/pale coat colour phenotypes, respectively, have been described in a large number of mammals including, for example, mice (Robbins et al, 1993), humans (Valverde et al, 1995) and several farm animals like cattle (Klungland et al, 1995;Joerg et al, 1996;Rouzaud et al, 2000), pigs (Kijas et al, 1998 and, horses (Marklund et al, 1996), dogs (Everts et al, 2000;Newton et al, 2000), cats (Eizirik et al, 2003;Peterschmitt et al, 2009), rabbits (Fontanesi et al, 2006) and goats (Fontanesi et al, 2009a). In sheep, classical genetic studies have identified two alleles at the Extension locus: the dominant black (E D ) allele caused by two missense mutations in the MC1R gene (p.M73K and p.D121N) and present in the Norwegian Dala, Corriedale, Damara, Black Merino, Black Castellana and Karakul breeds (Vå ge et al, 1999 andRoyo et al, 2008); and the wild type (E 1 ) allele widely distributed in most breeds (Searle, 1968;Sponenberg, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…There have been three main functional alleles found at the MCIR locus determining coat colour in Bos taurus (Klungland et al 1995;Joerg et al 1996), with some additional variants reported (Vanetti et al 1994;Rouzaud et al 2000;Graphodatskaya et al 2000Graphodatskaya et al , 2002. The E D allele is due to a Leu99Pro amino acid change and considered dominant (Klungland et al 1995).…”
mentioning
confidence: 99%